GIS-Based Mapping of Flood Vulnerable Areas in Iskandar Puteri - Jeffrey Zulkifli, Yuszaimi; Saifullizan Mohd Bukari (Recent Trends in Civil Engineering and Built Environment, 2025)
The flooding near the Sultan Ibrahim Stadium on Jalan J4, Jalan Gelang Patah, Iskandar Puteri is attributed to the ongoing development and construction projects near Sungai Danga, impacting the drainage system. The Department of Irrigation and Drainage (DID) reported that on December 24, 2021, the flood depth on Jalan J4 ranged from 0.1 to 0.3 meters, with heavy rainfall reaching an average of 71 mm within a one-hour period, classified as "very heavy" by DID. This requires an important understanding of the relationship between land use patterns and flood risk for effective mitigation. This project aims to produce flood risk maps using Geographic Information Systems (GIS) applications and examine the topography and land use class resulting from the data obtained. Global Positioning System (GPS) aids in gathering data for later analysis. Classifying land use using Semi-Automatic Classification Plugin (SCP) analysis and obtaining contours by raster extraction. The results of the study are maps showing flood risk based on categorized land use. This allows authorities to engage in strategic planning aimed at addressing and mitigating the flood issue.